THE IMPACT OF SERVICE QUALITY, TRUST ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING AT J&T LHOKSEUMAWE CITY - Anwar; Adnan; Teuku Zulkarnaen; Naufal Bachri; Rusydi Abubakar; Heriyana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research is to examine the influence of service quality and customer trust on customer loyalty at PT. Global Jet Express (J&T) in Lhokseumawe with customer satisfaction as a mediating or intervening variable. This research uses a quantitative approach by collecting data using a questionnaire using Google Form. The data obtained was then processed using SmartPLS 3.0 analysis with the intervening effect. The analysis used includes: measurement model evaluation, structural model evaluation, and model fit evaluation. The results of this study show that the results of the H6 analysis test show that CS is able to mediate significantly and positively the influence of SQ on CL. This means that customer satisfaction can mediate or strengthen the service quality variable on customer loyalty at the J&T company. H7 shows that CS is able to mediate significantly and positively the effect of CT on CL. The higher the level of service quality and information access that the J&T expedition company has, the stronger the influence of customer trust will be on customer loyalty. This research can be a reference for J&T Lhokseumawe in designing strategies and policies to improve service quality and service access quality and increase trust in customers.